1996
DOI: 10.1149/1.1837249
|View full text |Cite
|
Sign up to set email alerts
|

p‐ and n‐Type Silicon Electrochemical Properties in Dilute Hydrofluoric Acid Solutions

Abstract: electrodes with surface films which are porous and rough on their solution side. Li deposition in LiPF6 solutions was found to be more uniform than in LiClO4 solutions. This correlates very well with previous studies (Fourier transform infrared, energy dispersive x-ray spectroscopy, and x-ray photoelectron spectroscopy) which revealed that different surface chemistries are developed on the electrodes in these systems.9 In LiC1O4 solutions the surface films comprise a mixture of ROCO2Li, Li2CO3, Li halides, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…It was found that when silicon wafers are immersed in 15%-30% HF, the lowest surface recombination is attained. This occurs because the HF concentration is high enough to passivate most of the silicon dangling bonds with hydrogen, and provides a field effect passivation mechanism by retaining a high surface charge caused by a difference in the silicon Fermi level and reduction potential of the HF solution 23 . The choice of 15% HF was for safety reasons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that when silicon wafers are immersed in 15%-30% HF, the lowest surface recombination is attained. This occurs because the HF concentration is high enough to passivate most of the silicon dangling bonds with hydrogen, and provides a field effect passivation mechanism by retaining a high surface charge caused by a difference in the silicon Fermi level and reduction potential of the HF solution 23 . The choice of 15% HF was for safety reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Another important addition to the HF solution was the inclusion of HCl. By adding a small amount of HCl in the 15% HF solution, the hydrogen concentration in the HF solution is increased, which in turn increases the amount of hydrogen available for the surface passivation of silicon wafers, allowing the bulk silicon lifetime to be obtained post illumination 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it is possible to measure band-bending at the silicon-electrolyte interface using electrochemical based techniques. [25,26] By this method a potential difference is applied across a silicon wafer and counter electrode immersed in an electrolytic solution (e.g., HF). By varying the potential, information regarding space charge capacitance can be inferred, and the resulting band bending can be determined.…”
Section: Energy Levels At the Silicon-electrolyte Interface And The Imentioning
confidence: 99%